LA TRIANGULACIÓN MÚLTIPLE EN LA INVESTIGACIÓN-ACCIÓN CON EJEMPLOS DE INVESTIGACIÓN PROPIA - Majewska, Renata (Neofilolog, 2020)
The aim of the article is to reflect upon the possibilities offered by triangulation in qualitative research, with particular emphasis placed on action research. Various types of triangulation have been presented, including the most recommended multiple triangulation. A variety of advantages and functions of triangulation have been shown, first and foremost the ones which refer to dynamic, systemic and multicausal phenomena. All the theoretical considerations have been illustrated by the author’s own research conducted in Poland, in one of the bilingual sections with Spanish language in the secondary school. The research concerned the development of students’ discursive competence within the genre of an intercultural comparison, and its conditioning. The research used multiple triangulation: of data sources, of researchers, of methods and of data analysis, as well as temporal and special triangulation. The investigation is finished with conclusions of methodological nature.